Selecting candidate V-type asteroids from the analysis of the Sloan Digital Sky Survey colors - Roig, F. (2006)
We present a systematic method to identify possible basaltic (V-type) asteroids using the Moving Objects Catalog (MOC) of the SDSS. The method is based on the Principal Components Analysis of the MOC colors combined with some refined criteria of segregation of the taxonomic classes. We found several V-type candidates outside the Vesta family, most of them in the inner asteroid belt. We also identified a few candidates in the middle/outer belt. Notwithstanding, their basaltic nature still needs to be conformed by spectroscopy, and these candidates are potential targets for observation using large telescopes.